2019
DOI: 10.1073/pnas.1818816116
|View full text |Cite
|
Sign up to set email alerts
|

Historical roots of implicit bias in slavery

Abstract: Implicit racial bias remains widespread, even among individuals who explicitly reject prejudice. One reason for the persistence of implicit bias may be that it is maintained through structural and historical inequalities that change slowly. We investigated the historical persistence of implicit bias by comparing modern implicit bias with the proportion of the population enslaved in those counties in 1860. Counties and states more dependent on slavery before the Civil War displayed higher levels of pro-White im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
137
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 172 publications
(144 citation statements)
references
References 39 publications
3
137
1
3
Order By: Relevance
“…Indeed, even if we only recruited European Americans living in the US, participants were likely to come from states/cities having a non‐homogeneous cultural knowledge about African versus European Americans. In line with this idea, we know from previous work that there is meaningful variability in the racial bias due to cities and counties (Hehman, Flake, & Calanchini, ; Orchard & Price, ; Payne, Vuletich, & Brown‐Iannuzzi, ; Zerhouni, Rougier, & Muller, ). Any inter‐individual variability (or differences in inter‐individual variability between the VAAST and the IAT) could thus be explained by a variability in cultural exposure.…”
Section: Introductionmentioning
confidence: 55%
“…Indeed, even if we only recruited European Americans living in the US, participants were likely to come from states/cities having a non‐homogeneous cultural knowledge about African versus European Americans. In line with this idea, we know from previous work that there is meaningful variability in the racial bias due to cities and counties (Hehman, Flake, & Calanchini, ; Orchard & Price, ; Payne, Vuletich, & Brown‐Iannuzzi, ; Zerhouni, Rougier, & Muller, ). Any inter‐individual variability (or differences in inter‐individual variability between the VAAST and the IAT) could thus be explained by a variability in cultural exposure.…”
Section: Introductionmentioning
confidence: 55%
“…Previous research therefore generally utilized this operationalization of explicit bias (e.g. Connor, Sarafidis, Zyphur, Keltner, & Chen, 2019; Hehman et al, 2018; Leitner et al, 2016a; Leitner et al, 2016b; Payne et al, 2019). The difference scores computed for each participant were subsequently used to compute two scores per county: the average local difference score (interpreted as regional bias) and the standard deviation of the local difference scores (interpreted as local disagreements in bias).…”
Section: Methodsmentioning
confidence: 99%
“…What factors lead to the local emergence of hostile online environments? Online hostility can emerge from current local events (Williams & Burnap, 2015) or local history (Payne, Vuletich, & Brown‐Iannuzzi, 2019). For example, Kaakinen, Oksanen, and Räsänen (2018) observed that the Paris terror attack from November 2015 was associated with a rise in fear and intergroup hostility among Finnish internet users, who related to the pre‐attack situation of their fellow Europeans (c.f., Oksanen et al, 2018).…”
Section: Regional Attitudes Towards Minorities and Online Hostilitymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, on average in the US, scientists are expected to be male (e.g., Miller, Nolla, Eagly, & Uttal, 2018) and Black men are expected to be dangerous (e.g., Oliver, 2003). Such stereotypes are transmitted in overt and implicit ways through the mass media and other forms of socialization; people can learn and reinforce them without meaning to do so (e.g., Arendt, 2013; Kohne et al, 2020;Lyons & Kashima, 2003;Payne, Vuletich, & Brown-Iannuzzi, 2019). Above and beyond positive or negative attitudes towards social groups (i.e., outgroup prejudice and ingroup preference), the descriptive content of cultural stereotypes affects how people are treated and dictates the specific forms of discrimination to which they are vulnerable (Bodenhausen et al, 1998).…”
Section: Introductionmentioning
confidence: 99%